Applications of Lewis Acid Gold(I) Catalysis in the Synthesis of Polycyclic Carbocycles and the Total Synthesis of (±)-Salvinorin A - Tran, Huy Minh (Université d'Ottawa / University of Ottawa, 2022)
For most of human history, precious metals such as gold, silver, and platinum were used as currency and jeweler. Beginning in the 20th century, with the onset of transition metal catalysis, chemists developed new methods to support industrial chemical synthesis. There are many notable examples, one is the Ziegler-Natta catalysts to perform olefin polymerization using titanium/aluminum-based systems. Another is the Fisher-Tropsch process to convert synthesis gas (CO/H2) into liquid hydrocarbons typically using cobalt, ruthenium, and iron. Also, the Haber-Bosch process where nitrogen and hydrogen gases are reacted in the presence of an iron catalyst to generate ammonia is a critically important process for the production of agricultural fertilizer worldwide. For precious transition metals such as gold, the first report of the metal being used in homogenous catalysis was in 1986. In this thesis, the application of gold homogenous into the synthesis of polycyclic carbocycles is being reported. This method was designed as a three-step one-pot sequence where an initial Diels-Alder reaction forms the first carbocycle with an embedded silyl enol ether moiety reactive to homogenous gold(I) catalysis. By selecting specific catalyst ligand and solvent conditions, selectivity between tri or steroid-like tetracycles was achieved via gold then Prins cyclizations or gold then Diels-Alder cyclizations. A combined total of 31 examples across 3 scopes was demonstrated using this divergent and modular strategy. This methodology aims to be applied in medicinal chemistry research in the synthesis of libraries of structurally related compounds baring resemblance to bioactive natural products. A related synthetic strategy was also used by our group in the total synthesis of salvinorin A. Initially isolated from Salvia divinorum in 1972, salvinorin A is trans neo-clerodane diterpene and was found to be a selective agonist of the kappa opioid receptor (κOR). This is unique compared to traditional morphine type opioids which are substrates of mu (μOR) and delta (δOR) opioid receptors. And as such, extensive work in medicinal chemistry has been published on utilizing salvinorin A as starting point towards the development of new analgesics. Our approach to synthesize salvinorin A centered around using a Diels-Alder reaction then gold cyclization to form the AB rings. The remaining C ring was formed via gold photoredox catalyzed radical cyclization, 1,2-addition of a furanyl organotitanium, and palladium catalyzed carbonylation. The formal synthesis of salvinorin A was completed in 21 steps by intercepting an intermediate in Hagiwara’s reported synthesis, and addition 3 steps would complete the total synthesis.
Keywords: Organic Chemistry; Gold Catalysis; Total Synthesis; Organic Methodology